Wind pressure distribution characteristics of ancient Chinese timber lounge bridges based on the wind tunnel test - Xiaoyue Gao; Qing Chun; Yidan Han (Journal of Wood Science)
Abstract Timber lounge bridges are architecturally significant ancient bridges in China. They have unique shapes and gentle structures that are particularly vulnerable to wind loads. Owing to their uniqueness, the wind pressure distribution characteristics of these bridges differ from those of ordinary buildings or bridges. Therefore, to explore these characteristics, refined, scaled, and rigid models of beam- and arch-type lounge bridges were produced using 3D printing technology. Wind pressure tests in wind tunnels were conducted for different bridge span structures and open states of lounge houses. The results showed that in most cases, the influence of the bridge span structure on the wind pressure on the lounge bridge roof was negligible. However, for a fully closed lounge house, the presence of weatherboards in the bridge span structure significantly increased the negative wind pressure on the roof. The difference in the wind pressure distribution among the three states—fully open, semi-open, and fully closed—was evident. Based on the findings, removing the upper weatherboards on the bridge house and the weatherboards for arches during high wind speeds, effectively change the direction of forces on the roof, thereby lowering the possibility of the roof being blown upwards.